Preparation method of corrosion-resistant coating of aluminum alloy heat exchanger

By combining pulsed laser with weak alkaline electrolyte solution, a dense oxide layer was prepared, which solved the problem of corrosion of aluminum alloy heat exchangers in the chloride environment, and significantly improved its corrosion resistance and mechanical strength.

CN119800345APending Publication Date: 2025-04-11GUANGXI SPECIAL EQUIP SUPERVISION & INSPECTION INST P R CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510046201.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Aluminum alloy heat exchangers are prone to corrosion problems in chloride environments, resulting in increased structural damage and maintenance costs. The corrosion-resistant coatings of the prior art are insufficient in chlorine-rich environments.

Method used

A dense and uniform oxide layer containing γ-Al2O3 crystal phase is prepared by combining pulsed laser with weakly alkaline electrolyte solutions (such as sodium borate solution) by laser-induced plasma on the surface of aluminum alloy heat exchangers.

Benefits of technology

It significantly improves the corrosion resistance and mechanical strength of aluminum alloy heat exchangers, overcomes the shortcomings of traditional methods in high temperature and high pressure environments, and provides long-term and stable protection effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800345A_ABST
    Figure CN119800345A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a corrosion-resistant coating of an aluminum alloy heat exchanger, which innovatively combines pulse laser with a weakly alkaline electrolyte solution, namely sodium borate, and adopts the pulse laser to replace a high-voltage electric field in micro-arc oxidation. A compact and uniform oxide layer is prepared on the surface of the aluminum alloy heat exchanger through laser-induced plasma, and the oxide layer comprises a gamma-Al2O3 crystal phase and has remarkable corrosion resistance. According to the technology, the problems that pitting corrosion, stress corrosion cracking and the like are likely to happen to a traditional aluminum alloy heat exchanger in the chlorine-rich environment can be effectively solved, and the corrosion resistance and durability of the aluminum alloy heat exchanger under the complex working condition are improved. In addition, according to the method, the mechanical strength of the aluminum alloy heat exchanger is remarkably improved, and the defect that the strength of the aluminum alloy heat exchanger is insufficient in the high-temperature and high-pressure environment is overcome. By means of the method, the anti-corrosion oxidation layer with the gamma-Al2O3 crystal phase can be manufactured in a low-cost and efficient mode, and lasting and stable performance guarantee is provided for the aluminum alloy in the complex industrial environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material surface modification, and in particular to a method for preparing a corrosion-resistant coating of an aluminum alloy heat exchanger. Background Art

[0002] Heat exchangers are key equipment for efficient heat exchange between cold and hot fluids, and play a vital role in the cooling systems of power systems and nuclear power plants. Take the shell and tube heat exchangers widely used in the industrial field as an example, especially the seawater heat exchanger, which is designed to allow seawater to flow in the tube side, while hot fluids such as steam and hot water circulate in the shell side. Through this structural layout, the cold and hot fluids exchange heat on the wall of the heat exchange tube, thereby effectively reducing the temperature of the hot fluid. After decades of development, the commonly used heat exchange tube materials are mainly copper alloys and titanium alloys. However, in actual use, erosion corrosion and corrosion perforation often occur. In contrast, aluminum alloys have broad application prospects in heat exchangers due to their excellent thermal conductivity, specific strength, corrosion resistance, easy processing and excellent weldability.

[0003] However, in actual service, aluminum alloy heat exchangers are prone to serious corrosion problems, especially when in contact with chloride media (such as seawater), which in turn damages the integrity of the structure and significantly increases maintenance costs. Specifically, aluminum alloys are prone to local corrosion, stress corrosion cracking, and pitting in chloride environments, especially under conditions of high temperature, high humidity, and high flow rates. The root cause is the natural oxide film (Al2O3) formed on the surface of aluminum alloys. 2 O 3 ) usually have problems such as poor uniformity, strong porosity and amorphous state, resulting in poor integrity of the protective layer. Therefore, the oxide layer is easily affected by the penetration of chloride ions, further destroying the protective effect of the metal matrix and causing corrosion to intensify. In addition, the chemical stability of aluminum alloy itself is poor. Under extreme environmental conditions (such as seawater or industrial coolants containing chlorides), electrochemical corrosion may occur, and even perforations may form on the tube wall of the heat exchanger, causing reduced heat transfer performance and equipment failure. As the corrosion deepens, the mechanical properties of the aluminum alloy will also be significantly affected, resulting in embrittlement and reduced strength of the material, which may eventually lead to premature failure of the equipment. Therefore, how to effectively improve the corrosion resistance of aluminum alloys in chloride environments has become an important topic of current research.

[0004] Conventional surface treatment methods, including coating, electroplating, anodizing, plasma electrolytic oxidation (PEO), and micro-arc oxidation (MAO), have been widely studied to mitigate corrosion. However, these methods face challenges such as environmental risks, high energy consumption, or limited durability in harsh environments. Among them, MAO has become a promising method due to its ability to form a dense ceramic oxide layer through high-voltage electrolysis and plasma-assisted processes. Weakly alkaline electrolyte solutions, such as NaSiO3, play a vital role in this process. These electrolytes not only contribute to the growth of the oxide film and the dissipation of heat, but also participate in the oxidation reaction as an oxygen source to generate the oxide layer, forming a composite ceramic coating with significantly improved corrosion resistance and mechanical strength. However, high energy consumption, defect formation caused by thermal stress, and the requirement for additional cooling equipment limit the industrial-scale application of MAO. At the same time, pulsed lasers, which can also provide plasma, do not have these disadvantages due to their very small thermal effect.

[0005] Pulse laser technology has attracted more and more attention due to its precision, energy concentration and environmental friendliness. When applied to aluminum alloys, pulse laser can clean surface contaminants, refine grains and generate a dense oxide layer, thereby enhancing corrosion resistance. In a certain literature, high-speed laser cladding and strengthening materials such as Y 2 O 3When used in combination, it has been shown that dense coatings with refined grains and enhanced mechanical properties and corrosion resistance can be produced. Techniques such as laser shock processing (LSP) and laser powder bed fusion (LPBF) have also been shown in a certain literature to significantly improve the mechanical properties of metal alloys, including strength and corrosion resistance. Similarly, selective laser melting (SLM) in a certain literature is able to produce fine-grained structures and low porosity, providing excellent corrosion resistance and biomedical properties. Pulsed laser technology, including nanosecond, picosecond and femtosecond lasers, can provide a certain degree of corrosion resistance in addition to laser cleaning. A study used pulsed lasers to clean cultural relics, which not only protected the integrity of the cultural relics themselves, but also provided a certain degree of corrosion resistance, thereby preventing further deterioration. In addition, there are studies that use pulsed lasers to combine ultrafast ablation with chemical oxidation to create micro / nano structures with excellent wettability and durability, promoting the manufacture of superhydrophobic surfaces. On the basis of this superhydrophobic surface, a certain literature pointed out that the introduction of hydrophobic groups through subsequent chemical modification can further enhance surface wettability and reduce corrosion rates. A study demonstrated that laser-induced technology can simplify the manufacture of superhydrophobic graphene. The rapid heating and cooling cycles of the pulsed laser form a high-temperature, high-pressure interface, driving plasma-assisted reactions that modify the surface and crystal structure, ultimately improving material properties. Despite these advances, some challenges remain: laser additive manufacturing requires large energy inputs and expensive reinforcement materials, laser cleaning provides insufficient corrosion resistance in chlorine-rich environments, and laser-made superhydrophobic surfaces often lack strength and durability, limiting their corrosion protection capabilities.

[0006] The corrosion-resistant coating manufactured by laser additive manufacturing in the existing technology requires a large amount of energy input and expensive reinforcement materials. The corrosion-resistant coating of the aluminum alloy heat exchanger provides insufficient corrosion resistance in a chlorine-rich environment. The surface of the corrosion-resistant coating of the aluminum alloy heat exchanger often lacks strength and durability, which limits their anti-corrosion ability.

[0007] Therefore, there is an urgent need to develop a method for preparing a corrosion-resistant coating for an aluminum alloy heat exchanger. Summary of the invention

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0009] A method for preparing a corrosion-resistant coating for an aluminum alloy heat exchanger comprises the following steps:

[0010] (1) preparing a hydrogen peroxide solution, wherein the concentration of the hydrogen peroxide solution is 2 to 3 g / L; preparing a sodium borate solution, wherein the concentration of the sodium borate solution is 10 to 12 g / L; mixing the hydrogen peroxide solution and the sodium borate solution to obtain a prepared solution;

[0011] (2) Grinding the surface of the aluminum alloy heat exchanger on which the coating is to be prepared;

[0012] (3) Immerse the aluminum alloy heat exchanger in the prepared solution so that the liquid surface covers the upper surface of the aluminum alloy heat exchanger by 4-5 mm;

[0013] (4) Adjust the parameters of the pulse laser beam modulation device, and drive the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy heat exchanger 30-35 times through the two-dimensional mobile platform;

[0014] (5) After the scanning is completed, the aluminum alloy heat exchanger is cooled in the prepared solution for 0.5-1h, ultrasonically cleaned with anhydrous ethanol for 10-15min, and taken out and dried at room temperature for 20-24h, so that a corrosion-resistant coating of the aluminum alloy heat exchanger is formed on the surface of the aluminum alloy heat exchanger.

[0015] Preferably, in step (2), the surface of the aluminum alloy heat exchanger is polished with sandpaper having a particle size of 240#, 500#, and 800#, respectively.

[0016] Preferably, the concentration of the sodium borate solution in the prepared solution in step (1) is 12 g / L. Too high a concentration of sodium borate will increase the corrosion current density, while too low a concentration will cause the surface γ-Al 2 O 3 The crystalline content is reduced.

[0017] Preferably, the concentration of hydrogen peroxide in the prepared solution in step (1) is 3 g / L.

[0018] Preferably, the solution prepared in step (3) covers the upper surface of the aluminum alloy heat exchanger by 4 mm.

[0019] Preferably, in step (4), the power of the pulse laser beam modulation device is 80-90 W, the pulse frequency is 490-500 kHz, and the pulse width is 210-220 ns.

[0020] Furthermore, the optimal focal length of the pulse laser beam modulation device is 25.5 cm.

[0021] Furthermore, in step (4), the pulse laser beam modulation device has a power of 80 W, a pulse frequency of 500 kHz, and a pulse width of 220 ns.

[0022] Furthermore, in step (4), the two-dimensional mobile platform scans back and forth 30 times.

[0023] Furthermore, in the step (5), the aluminum alloy heat exchanger is cooled in the prepared solution for 1 hour, ultrasonically cleaned with anhydrous ethanol for 10 minutes, and then taken out and dried at room temperature for 24 hours.

[0024] Due to the adoption of the above technical solution, the present invention has the following technical advances compared with the prior art:

[0025] 1) This application innovatively combines pulsed laser with weak alkaline electrolyte solution - sodium borate, uses pulsed laser to replace the high voltage electric field in micro-arc oxidation, and prepares a dense and uniform oxide layer on the surface of the aluminum alloy heat exchanger by laser-induced plasma. The oxide layer contains γ-Al 2 O 3 Crystalline phase, with significant anti-corrosion performance. This technology can effectively overcome the problems of traditional aluminum alloy heat exchangers prone to pitting and stress corrosion cracking in chlorine-rich environments, and improve their corrosion resistance and durability under complex working conditions. In addition, this method also significantly improves the mechanical strength of aluminum alloy heat exchangers, overcoming the shortcomings of aluminum alloy heat exchangers themselves in high temperature and high pressure environments.

[0026] 2) The weakly alkaline sodium borate is combined in the preparation process, which is low in cost and pollution-free to the environment, and conforms to the concept of green environmental protection. At the same time, the power requirement of the entire preparation process is low, which can save a lot of energy, and the thermal effect is small, and no additional cooling equipment is required, which further reduces the production cost. Through this method, γ-Al can be manufactured in a low-cost and efficient manner. 2 O 3 The crystalline anti-corrosion oxide layer overcomes the defects of traditional aluminum alloy surface treatment technology and provides long-lasting and stable performance guarantee for aluminum alloy in complex industrial environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0028] Figure 1 These are the surface micromorphologies of samples AA0, AA1, and AA2 under the secondary electron mode of a scanning electron microscope.

[0029] Figure 2 These are the electrochemical corrosion test results of three samples: AA0, AA1, and AA2. DETAILED DESCRIPTION

[0030] The following embodiments may help those skilled in the art to more fully understand the present invention, but shall not limit the present invention in any way.

[0031] Example

[0032] A method for preparing a corrosion-resistant coating for an aluminum alloy heat exchanger comprises the following steps:

[0033] (1) preparing a hydrogen peroxide solution, wherein the concentration of the hydrogen peroxide solution is 2 to 3 g / L; preparing a sodium borate solution, wherein the concentration of the sodium borate solution is 10 to 12 g / L; mixing the hydrogen peroxide solution and the sodium borate solution to obtain a prepared solution;

[0034] (2) Grinding the surface of the aluminum alloy heat exchanger on which the coating is to be prepared;

[0035] (3) Immerse the aluminum alloy heat exchanger in the prepared solution so that the liquid surface covers the upper surface of the aluminum alloy heat exchanger by 4-5 mm;

[0036] (4) Adjust the parameters of the pulse laser beam modulation device, and drive the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy heat exchanger 30-35 times through the two-dimensional mobile platform;

[0037] (5) After the scanning is completed, the aluminum alloy heat exchanger is cooled in the prepared solution for 0.5-1h, ultrasonically cleaned with anhydrous ethanol for 10-15min, and taken out and dried at room temperature for 20-24h, so that a corrosion-resistant coating of the aluminum alloy heat exchanger is formed on the surface of the aluminum alloy heat exchanger.

[0038] In one embodiment of the present invention, in step (2), the surface of the aluminum alloy heat exchanger is polished with sandpapers having particle sizes of 240#, 500#, and 800#, respectively.

[0039] In one embodiment of the present invention, the concentration of the sodium borate solution in the prepared solution in step (1) is 12 g / L. Too high a concentration of sodium borate will increase the corrosion current density, while too low a concentration will cause the surface γ-Al 2 O 3 The crystalline content is reduced.

[0040] In one embodiment of the present invention, the concentration of hydrogen peroxide in the prepared solution in step (1) is 3 g / L.

[0041] In one embodiment of the present invention, the solution prepared in step (3) covers the upper surface of the aluminum alloy heat exchanger by 4 mm.

[0042] In one embodiment of the present invention, in step (4), the power of the pulse laser beam modulation device is 80-90 W, the pulse frequency is 490-500 kHz, and the pulse width is 210-220 ns.

[0043] Furthermore, the optimal focal length of the pulse laser beam modulation device is 25.5 cm.

[0044] Furthermore, in step (4), the pulse laser beam modulation device has a power of 80 W, a pulse frequency of 500 kHz, and a pulse width of 220 ns.

[0045] Furthermore, in step (4), the two-dimensional moving platform scans back and forth 30 times at a scanning speed of 120 mm / min.

[0046] Furthermore, in the step (5), the aluminum alloy heat exchanger is cooled in the prepared solution for 1 hour, ultrasonically cleaned with anhydrous ethanol for 10 minutes, and then taken out and dried at room temperature for 24 hours.

[0047] In one embodiment of the present invention, the model of the pulse laser beam modulation device is HGTECH LSF200C.

[0048] Experimental example

[0049] (1) Cutting the aluminum alloy heat exchanger or aluminum alloy metal block to obtain three identical aluminum alloy blocks, and polishing them with sandpaper of 240#, 500#, and 800# grit for later use;

[0050] (2) Number the three aluminum alloy blocks respectively as AA0, AA1, and AA2.

[0051] (3) The prepared solution was submerged 4 mm above the upper surface of AA1, the parameters of the pulse laser beam modulation device were adjusted, and the height of the pulse laser output device was adjusted to the optimal focal length. The pulse laser beam modulation device was driven by a two-dimensional mobile platform to scan back and forth on the surface of AA1 30 times, and the scanning speed was 120 mm / min; the power of the pulse laser beam modulation device was 80 W, the pulse frequency was 500 kHz, and the pulse width was 220 ns. After the scanning was completed, it was cooled in the prepared solution for 1 hour, and then ultrasonically cleaned with anhydrous ethanol for 10 minutes, and then taken out and dried at room temperature for 24 hours.

[0052] (4) Directly use a pulse laser beam modulation device driven by a two-dimensional mobile platform to scan back and forth on the surface of AA2 30 times, with a scanning speed of 120 mm / min; the pulse laser beam modulation device has a power of 80 W, a pulse frequency of 500 kHz, and a pulse width of 220 ns. After scanning, cool and dry in air for 25 hours.

[0053] The surface oxide layer microstructure of AA0, AA1 and AA2 was analyzed in turn. The results can be seen in Figure 1 ,pass Figure 1 It can be concluded that after the AA1 sample was treated with weak alkaline solution and pulsed laser induced plasma, its surface was uniformly covered with a continuous oxide layer. Compared with the AA2 sample treated with pulsed laser alone, the oxide layer on the AA1 surface was more uniform and dense, and the number and size of pores were significantly reduced. This shows that the treatment method is effective in optimizing the microstructure of the oxide layer, thereby helping to provide long-term and stable protection in corrosive environments.

[0054] At the same time, electrochemical corrosion tests were carried out on AA0, AA1, and AA2; the results can be found in Figure 2 ,pass Figure 2 It can be concluded that after the AA1 sample was treated with pulsed laser induced plasma in sodium borate solution, the corrosion current density calculated by the Tafel extrapolation method of its polarization curve was significantly reduced, which was more than one order of magnitude lower than that of the AA2 sample, and the corrosion potential was increased by about 0.05V. This shows that the corrosion resistance of the AA1 sample is significantly better than that of the AA2 sample. The higher corrosion potential indicates that the coating can effectively block the intrusion of corrosive media, and the significant reduction in corrosion current density indicates that it is easier to form a dense protective layer or passivation film on the surface of the sample, which significantly improves the corrosion resistance of the oxide layer. Therefore, compared with the AA2 sample, the AA1 sample exhibits a better anti-corrosion effect.

[0055] The above generally describes the present invention in detail, but it is obvious to a person skilled in the art that some modifications or improvements can be made to the present invention. Therefore, modifications or improvements that do not depart from the spirit of the present invention are within the scope of protection of the present invention.

Claims

1. A method for preparing a corrosion-resistant coating for an aluminum alloy heat exchanger, characterized in that: The following steps are involved: (1) preparing a hydrogen peroxide solution, wherein the concentration of the hydrogen peroxide solution is 2 to 3 g / L; preparing a sodium borate solution, wherein the concentration of the sodium borate solution is 10 to 12 g / L; mixing the hydrogen peroxide solution and the sodium borate solution to obtain a prepared solution; (2) Grinding the surface of the aluminum alloy heat exchanger on which the coating is to be prepared; (3) Immerse the aluminum alloy heat exchanger in the prepared solution so that the liquid surface covers the upper surface of the aluminum alloy heat exchanger by 4-5 mm; (4) Adjust the parameters of the pulse laser beam modulation device, and drive the pulse laser beam modulation device to scan back and forth on the surface of the aluminum alloy heat exchanger 30-35 times through the two-dimensional mobile platform; (5) After the scanning is completed, the aluminum alloy heat exchanger is cooled in the prepared solution for 0.5-1h, ultrasonically cleaned with anhydrous ethanol for 10-15min, and taken out and dried at room temperature for 20-24h, so that a corrosion-resistant coating of the aluminum alloy heat exchanger is formed on the surface of the aluminum alloy heat exchanger.

2. The method for preparing the corrosion-resistant coating of the aluminum alloy heat exchanger according to claim 1, characterized in that: In step (2), the surface of the aluminum alloy heat exchanger is polished with sandpapers of 240#, 500#, and 800# grits in sequence.

3. The method for preparing the corrosion-resistant coating of the aluminum alloy heat exchanger according to claim 1, characterized in that: The concentration of the sodium borate solution in the prepared solution of step (1) is 12 g / L, and the concentration of the hydrogen peroxide in the prepared solution of step (1) is 3 g / L.

4. The method for preparing the corrosion-resistant coating of the aluminum alloy heat exchanger according to claim 1, characterized in that: In step (4), the power of the pulse laser beam modulation device is 80-90W, the pulse frequency is 490-500kHz, and the pulse width is 210-220ns.

5. The method for preparing the corrosion-resistant coating of the aluminum alloy heat exchanger according to claim 1, characterized in that: The optimal focal length of the pulse laser beam modulation device is 25.5cm.

6. The method for preparing the corrosion-resistant coating of the aluminum alloy heat exchanger according to claim 4, characterized in that: In step (4), the pulse laser beam modulation device has a power of 80 W, a pulse frequency of 500 kHz, and a pulse width of 220 ns.

7. The method for preparing the corrosion-resistant coating of the aluminum alloy heat exchanger according to claim 1, characterized in that: In step (4), the two-dimensional mobile platform scans back and forth 30 times.

8. The method for preparing the corrosion-resistant coating of the aluminum alloy heat exchanger according to claim 1, characterized in that: In the step (5), the aluminum alloy heat exchanger is cooled in the prepared solution for 1 hour, ultrasonically cleaned with anhydrous ethanol for 10 minutes, and then taken out and dried at room temperature for 24 hours.

9. The method for preparing the corrosion-resistant coating of the aluminum alloy heat exchanger according to claim 1, characterized in that: Step (3) The prepared solution covers the upper surface of the aluminum alloy heat exchanger by 4 mm.